2020
DOI: 10.1021/acs.jafc.0c01893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Red Yeast Rice on Metabolic Diseases: A Review of Possible Mechanisms of Action

Abstract: Metabolic diseases constitute a major public health burden and are linked with high morbidity and mortality. They comprise atherosclerosis dyslipidemia, diabetes, hypertension, and obesity. However, there is no single drug that can simultaneously treat multiple diseases with complex underlying mechanisms. Therefore, it is necessary to identify a class of adjuvant drugs that block the development of metabolic diseases from a preventive perspective. Red yeast rice is a food fermentation product widely used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…The meridian tropism of red yeast rice is the meridian of the large intestine, spleen, and liver [ 29 ]. Modern pharmacology has shown that red yeast rice exerts potential protective effects on the liver, pancreas, blood vessels, and intestines [ 2 ], which matches the functions to the meridians of the liver, stomach, heart, and small intestine, respectively. Therefore, the results of this study have reference significance for the treatment of diseases related to stomach, heart, and small intestine meridians by red yeast rice beyond the meridian of the large intestine, spleen, and liver [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meridian tropism of red yeast rice is the meridian of the large intestine, spleen, and liver [ 29 ]. Modern pharmacology has shown that red yeast rice exerts potential protective effects on the liver, pancreas, blood vessels, and intestines [ 2 ], which matches the functions to the meridians of the liver, stomach, heart, and small intestine, respectively. Therefore, the results of this study have reference significance for the treatment of diseases related to stomach, heart, and small intestine meridians by red yeast rice beyond the meridian of the large intestine, spleen, and liver [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As traditional Chinese medicinal material with dual functions of medicine and food, red yeast rice has been widely applied in food coloring, fermentation, cholesterol reduction, and other aspects [ 1 ]. In addition, the red yeast rice contains many bioactive substances, including multiple ketone isoflavones, plant sterols, and unsaturated fatty acids and [ 2 ]. The effect of red yeast rice cholesterol mainly comes from the monacolin K composition.…”
Section: Introductionmentioning
confidence: 99%
“…M. koenigii and M. minutum reduce the number of medications needed to treat many metabolic and non-communicable diseases, including diabetics, cancers, cardiovascular diseases, and obesity [ 9 , 10 , 11 , 12 ]. The majority of metabolic and non-communicable diseases are linked with higher mortality and morbidity rates [ 13 ]. Therefore, Nowadays, the research interests are more focused on evaluating the bioactivities of Natural products from herbal sources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research has showed that plant-based diets rich with medicinal herbs are low-risk interventions that lower body mass index (BMI), blood pressure, glycated hemoglobin (HbA1C), and cholesterol levels. Therapeutic herbs may also reduce the number of medications needed to treat many metabolic and noncommunicable diseases, including diabetes, cancers, cardiovascular diseases, obesity, and the majority of metabolic and noncommunicable diseases are linked with higher mortality and morbidity rates [ 5 ]. Curry leaves are the most common herb used in Asia with enormous nutritive and pharmacological benefits.…”
Section: Introductionmentioning
confidence: 99%